An Analysis of the Four Pārājikasikkhā in Samantapāsadikā According to the Current Thai Sangha Law - Khethong, Dr. Phramaha Khanob Sahayapanno; Yanasophano, Phramaha Sarawut; Ajarasupho, Phra Jaturong (Journal of Dhamma for Life, 2023)
This research article has the primary objectives are to delineate the evolutionary trajectory and historical development of the Samantapasādika, assess the four Pārājikā rulings articulated within the Samantapasādika, and evaluate these rulings in light of contemporary Thai Sangha law. The research methodology employed for this study is predominantly documentary. According to the research findings, the Samantapasādika serves as a commentary on various canonical texts, including the Vinaya Pitaka, the Mahavibhaṅga, the Bhikkhunī Vibhaṅga, the Mahavagga, the Chulavagga, and the Parivāra. The author, Phra Buddhakosajarn, adhered closely to the format of the original commentary penned by Kurundi and Maha-Atthakahamahapaccari. Upon analyzing Parajika 4, it was discerned that the Parajika Judgment follows a specific format for each point, comprising the reliance on multiple individuals for decision-making in the First Parajika. The Second Parajika mandates an in-depth investigation into the details of evidence across five dimensions: object, time, occasion, price, and use. The Third Parajika necessitates the examination of six aspects of legal evidence: objects, time, place, weapons, postures, and special gestures. Meanwhile, the Fourth Parajika entails an inquiry into six facets of credibility, encompassing the accomplishments of the individual, the method employed, time, place, defilements that can be eliminated, and Dhamma that has been accomplished. In contrast to the stipulations of the current Thai Sangha law, where the criteria for adjudicating the four Parajikā are not treated as discrete components, but rather decisions are rendered by applying overarching settlement rules. This departure signifies a shift from the originally prescribed Vinaya standards to a legalistic framework. Consequently, the Vinaya’s significance is perceived as diminished. Moreover, the protracted settlement procedure engenders misconceptions about the practice and results in delays in issue resolution, thereby adversely impacting the Sangha as a cohesive entity.